PELATIHAN KEORGANISASIAN KARANG TARUNA DWI MANUNGGAL DESA JAGAN BENDOSARI SUKOHARJO - Sukadi; Candra Budi Susila; Diana Rendrarini (Universitas Merdeka Madiun, 2023)
This Community Service activity was carried out as a form of youth organization Dwi Manunggal, Jagan Village, Bendosari, Sukoharjo in increasing the knowledge and abilities of members in planning and carrying out activities. Where the main problem faced by the youth committee is that youth members in planning and carrying out activities have begun to show a significant decline in enthusiasm, one of which is the lack of response to existing activities. To revive the spirit of youth organizations in planning and carrying out activities, organizational training activities were held for members of youth organizations Dwi Manunggal, Jagan Village, Bendosari, Sukoharjo. In the activity, it was also explained about the existing conditions or problems of the Dwi Manunggal youth organization and also the solutions. The results of this community service activity showed that based on the results of the discussion after the delivery of the material it was found that members of the Dwi Manunggal youth organization became more knowledgeable about an organization so that the Dwi Manunggal youth organization could become a place for good self-development of its members